Frontispiece: Fluorine‐18 Radiolabelling and Photophysical Characteristics of Multimodal PET–Fluorescence Molecular Probes. Issue 3 (14th January 2021) - Klenner, Mitchell A.; Pascali, Giancarlo; Massi, Massimiliano; Fraser, Benjamin H.
Abstract : PET–fluorescence multimodal probes provide complimentary information for medical diagnoses. Such probes enable specific functional imaging of a disease state from initial diagnostic positron emission tomography (PET) scans, followed by high spatial resolution, real‐time fluorescence imaging during intraoperative excision of the diseased tissue. Some of the most promising candidates for such imaging probes include quantum dots, rhenium(I) complexes, cyanine and BODIPY dyes, as well as other organic fluorophores. For more details see the Minireview by M. A. Klenner, B. H. Fraser et al. on page 861 .